Balancing immunity and tolerance: genetic footprint of natural selection in the transcriptional regulatory region of HLA-G - Gineau, L.; Luisi, P.; Castelli, E. C. [UNESP]; Milet, J.; Courtin, D.; Cagnin, N.; Patillon, B.; Laayouni, H.; Moreau, P.; Donadi, E. A.; Garcia, A.; Sabbagh, A. (Nature Publishing Group, 2015)
Human leukocyte antigen-G (HLA-G) has well-recognized immunosuppressive properties modulating the activity of many immune system cells, and polymorphisms observed at the HLA-G 5'upstream regulatory region (5'URR) may influence gene transcriptional regulation. In this study, we characterized the sequence variation and haplotype structure of the HLA-G 5'URR in worldwide populations to investigate the evolutionary history of the HLA-G promoter and shed some light into the mechanisms that may underlie HLA-G expression control. A 1.4-kb region, encompassing the known HLA-G regulatory elements, was sequenced in three African populations from Senegal, Benin and Congo, and data were combined with those available in the literature, resulting in a total of 1411 individuals from 21 worldwide populations. High levels of nucleotide and haplotype diversities, excess of intermediate-frequency variants and reduced population differentiation were observed at this locus when compared with the background genomic variation. These features support a strong molecular signature of balancing selection at HLA-G 5'URR, probably as a result of the competing needs to maintain both a maternal-fetal immune tolerance and an efficient host immune response to invading pathogens during human evolution. An extended analysis of a 300-kb region surrounding HLA-G revealed that this region is not involved in a hitchhiking effect and may be the direct target of selection.